Consumption of healthy and unhealthy foods by the African poor: Evidence from Nigeria, Tanzania, and Uganda. (18th August 2022) - Dolislager, Michael; Liverpool‐Tasie, Lenis Saweda O.; Mason, Nicole M.; Reardon, Thomas; Tschirley, David
Abstract: We use national Living Standards Measurement Study (LSMS) datasets from Nigeria, Tanzania, and Uganda to examine consumption by the rural and urban poor of "unhealthy foods" (including ultra‐processed foods such as sweets and sugary beverages) versus "healthy foods" beyond starchy staples (such as vegetables, beans, animal products, and fruits). Consumption of processed foods and nonstaples is often associated in policy discussion in Africa with middle‐class urban consumers rather than the poor. We analyzed household food consumption expenditure with Locally Weighted Scatterplot Smoothing (LOWESS) curves and augmented Engel regressions. We found that substantial shares of the consumption expenditure of the poor, both rural and urban, are on healthy and unhealthy foods. We found, surprisingly, that the poor's food consumption patterns do not differ sharply from the middle classes', in rural and urban areas, except for the case of ultra‐processed foods of which the poor still consume much less than the middle class. We found that the poor dedicate 25% of their food consumption expenditure to the category vegetables/beans, versus 22% and 17% by the lower‐middle and upper‐middle‐income strata. Fruits/animal products constitute 17% of the poor's consumption expenditure compared to 23% and 27% by the lower‐ and upper‐middle strata. Ultra‐processed food (e.g., sugar‐sweetened beverages) form 12% of the consumption of the poor, versus 20% and 32% for the lower‐ and upper‐middle strata. Shares are increasing with income starting at incomes well below the poverty line. Nonincome factors play important roles: e.g., rural off‐farm employment is associated with more consumption expenditure of processed foods by the poor due to the opportunity cost of time.